2009
DOI: 10.1002/jms.1699
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput method for on‐target performic acid oxidation of MALDI‐deposited samples

Abstract: An information-rich on-target performic acid oxidation method, which is compatible with alkylation for differentiation of free cysteine versus disulfide-containing peptides, is described. On-target oxidation is achieved using performic acid vapor to oxidize disulfide-containing peptides and/or small proteins on the matrix-assisted laser desorption/ionization (MALDI) sample deposits. The on-target oxidation method is preferred over solution-phase oxidation methods because (1) less sample handling is required, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In addition, the detection of the various states of cysteine oxidation-i.e., disulfide bonds (-S-S-), sulfenic (-SOH), sulfinic (-SO 2 H) or sulfonic (-SO 3 H) acidsis becoming increasingly important in many biological processes, including oxidative stress [9][10][11][12]. Sulfonic acid is the final oxidation product of many such processes, and negative ion MS has proven effective for the detection of [M -H] − ions from cysteic-acid-containing peptides [13][14][15]. To date, a limited number of studies on negative ion fragmentation of cysteic-acid-containing peptides have been reported [14].…”
Section: ) From the Parent [M -H]mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the detection of the various states of cysteine oxidation-i.e., disulfide bonds (-S-S-), sulfenic (-SOH), sulfinic (-SO 2 H) or sulfonic (-SO 3 H) acidsis becoming increasingly important in many biological processes, including oxidative stress [9][10][11][12]. Sulfonic acid is the final oxidation product of many such processes, and negative ion MS has proven effective for the detection of [M -H] − ions from cysteic-acid-containing peptides [13][14][15]. To date, a limited number of studies on negative ion fragmentation of cysteic-acid-containing peptides have been reported [14].…”
Section: ) From the Parent [M -H]mentioning
confidence: 99%
“…Dual protease digestion (trypsin followed by chymotrypsin) of RNase A was performed using previously described methods [15,21]. Briefly, RNase A was dissolved at 1 mg mL −1 in a 25 mM ammonium acetate buffer adjusted to pH 6.0 with 10 mM formic acid.…”
Section: Ribonuclease a Proteolytic Digestionmentioning
confidence: 99%
See 1 more Smart Citation
“…al . 39 only cysteine residues are affected by the treatment, and the on-target oxidation is not complicated by reactions with H, M, W or Y amino acid containing peptides.…”
Section: Resultsmentioning
confidence: 99%
“…The model peptides containing cysteine residues were oxidized using solution-phase performic acid oxidation as previously described [25,26]. Briefly, 50 μL of performic acid (1:19 hydrogen peroxide:formic acid) was used to resuspend ca.…”
Section: Solution-phase Performic Acid Oxidationmentioning
confidence: 99%